Residual strain analysis in polycrystalline aggregates using diffraction measurement and finite element modelling - Dini,D; Song,X; Zhang,SY; Korsunsky,AM (J STRAIN ANAL ENG, 2009)
This paper reviews some of the modelling and experimental techniques recently employed by the authors for the analysis of the macro- and mesoscopic behaviour of polycrystalline aggregates. A joined-up approach is used for assessing the deformation behaviour of polycrystalline materials at the macroscopic and grain levels, based on combining modelling using the crystal plasticity finite element (CPFE) method with experimental characterization by in situ loading and continuous lattice strain measurement by diffraction. The complementarity of the two methodologies is emphasized, as it helps to improve understanding of the physics underlying inelastic deformation, damage mechanisms, and fatigue crack initiation. The proposed approach is part of the attempt to develop a general framework that will enable reliable and accurate determination of the inhomogeneous fields of plastic strain, the regions of localized plasticity, and intergranular residual stresses. Examples are given of microscopically calibrated CPFE simulations being used to match the experimentally observed evolution of lattice stresses and strains in advanced structural alloys of industrial interest.